PENGAKUAN INDIGENOUS PEOPLE DI AUSTRALIA - Anna Yulia Hartati; Aileyas Kabo (LP2M, 2018)
This article describes the process of recognition ofIndigenous people in Australia of theAboriginal and Torres Strait Islanders. The 1967 Referendum is a new chapter and an openroad for Aboriginal people to try to regain the rights of those whoin the past were snatchedaway by the arrival of white people. The Aboriginal people and Torres Strait Islanderresidents were the first and the first to settle in Australia, long before the arrival of theEuropeans. Unfortunately, because at the time ofthe arrival of Europeans, Aboriginal peopleare still formed in tribes so far from civilized and civilized, as well as sovereign governments.Since the arrival of Europeans who claimed Australia as their territory of power, Aboriginalcommunities continueto experience discrimination. Starting from not being considered anAustralian ruler, it is not counted in the census of the population to be part of Australia, untilthere are very cruel controls against them, such as Aboriginal abolition, the aboriginalgeneration away from Aboriginal influence, until Aboriginal people are not allowed to enterAustralia. In fact, Aborigines get discrimination against public services as well, whencompared to other official Australian citizens. With the Australian Referendum raising theAboriginal issue began to pave the way for Aboriginal people to achieve their rights. With the1967 Referendum, Aboriginal people are counted in the Australian population census as partof an Australian citizen. In subsequent years, gradualdiscrimination begins to be abolishedin relation to race, ethnicity, or color. And finally, in 2013 it is stated in the constitution thatAustralia recognizes Aboriginal and Torres Strait Islanders as Australia's first inhabitants.This research uses qualitative description research method. Secondary data were obtainedthrough documentary studies, ie through magazines, newspapers, books and other sourcesrelated to this research topic.Keywords:Indigenous People,Discrimination, Referendum